Drinking habits as cofactors of risk for alcohol induced liver damage. Issue 6 (1st December 1997) - Bellentani, S; Saccoccio, G; Costa, G; Tiribelli, C; Manenti, F; Sodde, M; Croce', L Saveria; Sasso, F; Pozzato, G; Cristianini, G; Brandi; the Dionysos Study Group, G
Abstract : Background —The Dionysos Study is a cohort study of the prevalence of chronic liver disease in the general population of two northern Italian communities. It included 6917 subjects, aged 12–65 (69% of the total population). Aims —The aim of this part of the study was to examine the relationship of daily alcohol intake, type of alcoholic beverage consumed, and drinking patterns to the presence of alcohol induced liver damage in an open population. Patients and methods —6534 subjects, free of virus related chronic liver disease and participating in the first cross-sectional part of the study, were fully examined. Each subject underwent: (a) medical history and physical examination, (b) evaluation of alcohol intake using an illustrated dietary questionnaire, and (c) routine blood tests. More invasive diagnostic procedures were performed when indicated. Results —Multivariate analysis showed that the risk threshold for developing either cirrhosis or non-cirrhotic liver damage (NCLD) was ingestion of more than 30 g alcohol per day in both sexes. Using this definition, 1349 individuals (21% of the population studied) were at risk. Of these, only 74 (5.5% of the individuals at risk) showed signs of liver damage. The prevalence of "pure" alcoholic cirrhosis was 0.43% (30 of 6917), representing 2.2% of the individuals at risk, with a ratio of men to women of 9:1, while 44 (3.3% of the individuals at risk) showed persistent signs of NCLD. After 50 years of age, the cumulative risk of developing both NCLD and cirrhosis was significantly higher (p<0.0001) for those individuals who regularly drank alcohol both with and without food than for those who drank only at mealtimes. Conclusions —Our data show that in an open population the risk threshold for developing cirrhosis and NCLD is 30 g ethanol/day, and this risk increases with increasing daily intake. Drinking alcohol outside mealtimes and drinking multiple different alcoholic beverages both increase the risk of developing alcohol induced liver damage.